Community structure, population structure and topographical specialisation of Gyrodactylus (Monogenea) ectoparasites living on sympatric stickleback species - Raeymaekers, Joost A. M; Huyse, Tine; Maelfait, Hannelore; Hellemans, Bart; Volckaert, Filip A. M (Folia parasitologica, 2008)
In order to disentangle the contribution of host and parasite biology to host specificity, we compared the structure and population dynamics of the Gyrodactylus (von Nordmann, 1832) flatworm community living on sympatric three-spined Gasterosteus aculeatus L. and nine-spined Pungitius pungitius (L.) stickleback. Between April 2002 and March 2003, a small lowland creek was sampled monthly. Species identity of about 75% of the worms per host was determined with a genetic nuclear marker (ITS1). Each stickleback species hosted a characteristic gill- and fin-parasitic Gyrodactylus: G. arcuatus Bychowsky, 1933 and G. gasterostei Gläser, 1974 respectively infecting the three-spined stickleback, with G. rarus Wegener, 1910 and G. pungitii Malmberg, 1964 infecting the nine-spined stickleback. Host size and seasonal dynamics were strong determinants of parasite abundance. A strong interaction between host and parasite species determined infection levels and affected three levels of parasite organisation: community structure, population structure and topographical specialisation. Community and population structure were shaped by asymmetric cross-infections, resulting in a net transmission of the Gyrodactylus species typical of the nine-spined stickleback towards the three-spined stickleback. Host density was not a major determinant of parasite exchange. Aggregation and topographical specialisation of the Gyrodactylus species of the three-spined stickleback were more pronounced than that of the nine-spined stickleback.
Keywords: Population Dynamics; Sex Characteristics; populační dynamika; roční období; Ecosystem; zvířata; Time Factors; Seasons; Animals; časové faktory; velikost těla; nemoci ryb; Female; ekosystém; Trematoda; infekce červy třídy Trematoda; Male; ženské pohlaví; pohlavní dimorfismus; mužské pohlaví; Species Specificity; Trematode Infections; druhová specificita; Body Size; Fish Diseases; Smegmamorpha